The ends of the developmental state. Issue 2 (2nd April 2016) - Lincoln, David
ABSTRACT: Some proponents in the global South seek to promote development along the same lines as the industrially advanced East Asian developmental states. After comparing ideal-types and models, this article considers the idea of national developmental modelling and explores the literature about using the East Asian developmental states as a model. One of these modellers is the South African government, which has expressed developmental state aspirations without specifying whether or not it holds any particular model in mind. Although authoritarianism is not an inevitable and necessary condition, it has been a feature of many of the model developmental states, and the literature raises warnings about its resurgence in emergent developmental states.